Setting the basis for transient DNA transformation and transformant selection in the red macroalga Gracilariopsis lemaneiformis - Eléouët, Morgane; Zhang, Ni; Guo, Peng; Lei, Yuehua; Kong, Fanna; Sui, Zhenghong (Frontiers in Marine Science, 2023)
Gracilariopsis lemaneiformis (Gp. lemaneiformis) is an economically important agar-producing red alga applicable in the food and cosmetic industries. The genetic knowledge of this species is, however, limited, and genetic tools for studying and engineering it are lacking. This has limited the understanding of its developmental genetics and hindered the development of new strains, and developing genetic tools would allow to tackle these problems. Here, transient DNA transformation via microparticle bombardment is reported for the first time in this species, as well as efficient exogenous gene expression driven by the CaMV35S promoter, the endogenous GlAct1 promoter, and the Pyropia yezoensis PyAct1 promoter in the transformed branches. Moreover, the Blue Fluorescent Protein (BFP) is demonstrated to be a suitable reporter gene for studies in Gp. lemaneiformis. Screening of antibiotic sensitivity is needed for the development of transient DNA transformation, and selection of transformants is also reported in the alga. Hygromycin B (Hyg) is determined to be the most effective antibiotic for Gp. lemaneiformis selection. The Hyg resistance gene driven by the CaMV35S promoter is shown to confer resistance to Hyg at a concentration of 1 mg.ml-1, but no transformed individual could be regenerated so far. These results are promising for future refining of the experimental conditions, for instance, by using different promoters and developing techniques for facilitating the penetration of the DNA in the cells.